Diversifikasi Bisnis Astra International: Kunci Ketahanan di Tengah Fluktuasi Ekonomi - Lubis, Syahrina Zahara (Asosiasi Dosen Akuntansi Indonesia, 2024)
The purpose of this study is to analyze the impact of business diversification on PT Astra International Tbk's bottom line during periods of economic volatility. Quantitative research methods are used to examine the relationship between business diversification, employee workflow, and resilience to global economic changes. Analysis results indicate that business diversification significantly affects a company's ability to withstand economic fluctuations. Diversification that is implemented successfully reduces financial risk and increases the operational stability of the business. However, when a moderating variable such as economic conditions and industry competition are considered, the impact of diversification on company performance becomes insignificant. This study provides an important contribution to understanding diversification strategies in emerging markets like Indonesia.